Apgar Score and the Amount of Blood of Mother in Labour in Delayed Cord Clamping Period - Marlina, Marlina; Trianingsih, Indah; Sari, Adinda Juwita; Rosmadewi, Rosmadewi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
A delay in cutting the umbilical cord in infants can increase the Apgar score in infants who experience asphyxia. Besides that, it can prevent postpartum hemorrhage from occurring. Most deaths from postpartum hemorrhage occur during the first 24 hours after delivery. This increase in the Apgar value proves that the longer the delay in the umbilical cord is carried out, even until it doesn't pulsate, the better the baby's body will be, which results in an increase in hemoglobin in the baby's body. The population in this study were all mothers in the 3-4 stage of labor in the city area. Bandar Lampung. The sample is part of the number and characteristics possessed by the population with 120 maternal. It is known the length of time delayed cord Clamping is performed on babies born (<30 seconds) as many as 3 (2.5%) respondents, while umbilical cord clamping is delayed for 30-180 seconds as many as 117 (97.5%) respondents, the Apgar score in newborns in the category of mild asphyxia - not asphyxia as much as 100%, the amount of blood that came out <250 grams was 93 (77.5% ) respondents and the amount of blood that came out 250 grams were 27 (22.5%) respondents. Delayed cord clamping does not increase the incidence of asphyxia and bleeding in laboring mothers, so immediate umbilical cord clamping can be performed by observing the baby's birth condition.